Assessment of extra oral soft tissue, three-dimensional airway volume and quality of life: A monoblock therapy appliance in obstructive sleep apnea study / Mohd Shukri Hazni - Mohd Shukri, Hazni (2019)
This study aimed to assess the efficacy of a monoblock therapy appliance in the treatment of patients diagnosed with mild to moderate OSA in terms of three-dimensional pharyngeal airway volume and extraoral soft tissue for pre-and post-treatment using a CBCT data set and also to evaluate changes in the quality of life among patients receiving treatment. Methods: Twenty patients with mild to moderate obstructive sleep apnea diagnosed with polysomnography were screened for eligibility using inclusion and exclusion criteria. They were evaluated with the Sleep Apnea Quality of Life (SAQLI) questionnaire at T0, T1, T2 and T3 visit. Patients received a mandibular monoblock appliance (MAA), a single block appliance that titrated at 60% of the maximum mandibular protrusion with 5mm vertical opening between upper and lower incisors. Cone beam computed tomogram imaging (CBCT) were taken at T1 and T3 visit without the appliance in situ. The data then were analysed using a Materialise Interactive Medical Image Control System (MIMICS) software. Post-treatment data at T3 were collected after 6 months of treatment. Parameters were airway volume, chin throat-lower face angle, and Quality of Life changes between pre and post-treatment. Results were presented as a comparison of mean with standard deviation and paired t-test data for all parameters. The statistical significance was set at p < 0.05 with data analysed using intention to treat analysis protocol. Results: Twenty patients (n=8 male, n= 12 female) diagnosed with mild to moderate OSA were recruited. At T3, six subjects dropped out with 14 subjects remained. All 4 domains of the questionnaire (SAQLI) showed a significant improvement in the quality of life after 6 months of monoblock wear (p-value<0.05). There were no iv significant changes in oropharyngeal three-dimensional airway volume and extraoral soft tissues(p-value >0.05). The inter- and intra-correlation coefficient of three-dimensional airway volume was 0.98 and 0.99 respectively. The inter-correlation co-efficient of the extraoral soft tissue assessment was 0.98 and intra co-efficient correlation was 0.99. Conclusion: There were no difference in three-dimensional oropharyngeal airway volume and extraoral soft tissue with the use of MAA in patients diagnosed with mild to moderate Obstructive Sleep Apnea after six months wear. There was significant improvement in patient’s quality of life with the treatment using a disease-specific Malay version SAQLI.